Ketamine as an alternative to ECT in catatonia in elderly women with bipolar disorder: A case report - Sarma, Shanthi; Arunachalam, Arulmathy; Kamara, Memunatu; Branjerdporn, Grace (Frontiers in Psychiatry, 2023)
The following paper described two cases of patients with catatonic depression in bipolar disorder (BD) referred to our electroconvulsive therapy (ECT) service. Both were deemed not medically fit for ECT, and were, instead, treated with intravenous (IV) ketamine. Both responded with a resolution of symptoms, returning to baseline level of functioning. During the COVID-19 pandemic, given the risks associated with providing ECT (an aerosol generating procedure) and, in the context of limited resources, ketamine therapy for catatonia is a potentially beneficial alternative or supportive treatment to ECT that merits additional research.